YOHARMAN: WALI NAGARI AIA MANGGIH KECAMATAN LUBUK SIKAPING (2008-2013) - Putra, Rahmad Eka (Pendidikan Sejarah, 2014)
This thesis examines the Yoharman: Wali Nagari Aia Manggih Kecamatan Lubuk Sikaping (2008-2013). The writing is done as a leader in Nagari Yoharman Aia Manggih. Yoharman career began as Youth Chief and was honored as a pioneer youth, then see how policies are made while in Wali Nagari until won numerous awards. This thesis aims to describe the life history and family environment and the role Yoharman, Yoharman for acting as Wali Nagari. The method used in this paper is the historical method with the following steps: : heuristic, Source criticism, then interpret the facts and poured into a form of writing called general history historiography. The results showed that: first Yoharman lifes journey is not easy, he had undergone ups and downs in his career but never discouraged Yoharman in carrying out all the work, support of the family never stopped making Yoharman always patient and enthusiastic in the face of everything. Based on the research that has been conducted, it can be concluded that, Yoharman policies during his tenure as Wali Nagari was successful because the programs planned by Yoharman can run either, and proof of the success of the program can still be felt to this day, such as the preservation of traditional arts continue to evolve, increase agricultural output with the aid of fertilizers and seeds, and improve public facilities and infrastructure to support the economy of the community by working with the relevant governments.